Nurses’ knowledge and its determinants in surgical site infection prevention: A comprehensive systematic review and meta-analysis - Tesfaye Engdaw Habtie; Sefineh Fenta Feleke; Aregash Birhan Terefe; Addis Wondmagegn Alamaw; Melsew Dagne Abate (PLoS ONE, 2025)
Objective The objective of this systematic review and meta-analysis is to assess and synthesize the global evidence on the level of nurses’ knowledge and its determinants regarding the prevention of surgical site infections. Methods This systematic review and meta-analysis were conducted following strict methodological guidelines to ensure accuracy and reliability. Adhering to the 2020 PRISMA checklist, a systematic review and meta-analysis sought to establish the pooled proportion of nurse’s knowledge and its determinants regarding surgical site infection prevention globally. MeSH terms and keywords were included in the search. Data extraction, quality assessment, and analysis followed established protocols. Heterogeneity and publication bias was assessed using STATA version 17.0. Results A total of seventeen observational studies, with sample sizes ranging from 30 to 515 participants, were included in the final analysis in a global context. In this systematic review and meta-analysis, the pooled proportion of nurses with good knowledge of surgical site infection prevention is 62% (95% CI: 50–74%) when assessed using a dichotomous scale. However, when knowledge is measured using a three-point Likert scale, the pooled proportion of those with good knowledge drops to 46% (95% CI: 21–72%), with an additional 27% (95% CI: 16–38%) demonstrating fair or moderate knowledge. Conclusion and recommendation This systematic review and meta-analysis is the first to synthesize data on nurses’ knowledge of surgical site infection (SSI) prevention. The findings reveal poor knowledge levels, highlighting the need for targeted educational interventions globally. While the pooled odds ratio is not statistically significant, training, longer service years, and higher education improve SSI prevention knowledge by enhancing critical thinking, boosting confidence, and fostering adherence to evidence-based practices. Future research should focus on identifying factors influencing nurses’ knowledge, particularly through longitudinal and interventional studies. Policymakers should incorporate international guidelines such as those recommended by the World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC) into nursing curricula, supported by robust assessment tools and educator training, to improve knowledge transfer and implementation of best practices.